Methyl propiolate and 3-butynone: Starting points for synthesis of amphiphilic 1, 2, 3-triazole peptidomimetics for antimicrobial evaluation. Issue 20 (15th October 2017) - Bakka, Thomas A.; Strøm, Morten B.; Andersen, Jeanette H.; Gautun, Odd R.
Graphical abstract: Abstract: A library of 29 small 1, 4-substituted 1, 2, 3-triazoles was prepared for studies of antimicrobial activity. The pharmacophore model investigated with these substrates was based on small peptidomimetics of antimicrobial peptides and antimicrobials isolated from marine organisms from sub-arctic regions. Using methyl 1, 2, 3-triazole-carboxylates and 1, 2, 3-triazole methyl ketones prepared through "click" chemistry we were able to synthesize the different cationic amphiphiles through three steps or less. Several structural modifications to the lipopohilic side and hydrophilic sides of the amphiphiles were investigated and compared with regards to antimicrobial activity and cytotoxicity in particular. The most promising amphiphile10f displayed minimum inhibitory concentrations (MICs) between 4–16 µg/mL against Gram-positive Enterococcus faecalis, Staphylococcus aureus, Streptococcus agalacticae, and Gram-negative Escherichia coli and Pseudomonas aeruginosa . The decent level of antimicrobial activity and biofilm inhibition, short synthesis, and accessible reagents, makes this type of amphiphilic mimics interesting leads for further development.